The Introduction of Detailed Spatial Planning in Sleman Regency - Yuntoro, Agung; Mardiyono, Mardiyono; Amin, Fadillah; Sahara, Takayuki (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This study examined the possibilities of legalizing detailed spatial planning in Sleman regency. By using objectives analysis of project cycle management (PCM) method, 7 approaches were identified to introduce detailed spatial planning, namely: Motivation approaches, Central Government Policy Approaches, Law Enforcement Approaches, Relocation Approaches, Industrial Development Approaches, Business Development Approaches, and Coordination with Sultan’s office Approaches. From the 7 approaches, 4 approaches were selected most convincing combinations which are relocation approaches, industrial development approaches, business development approaches and coordination with sultan’s land approaches. The examination of its feasibility were conducted by interviewing stakeholders in Sleman regency whose result showed that the first 3 approaches could be realized without serious problems while coordination with sultan’s land office approaches had to be handled with care because the authority of sultan’s land conversion was under the sultan’s office even though the location was in Sleman. To overcome these difficulties, Sleman regency must take initiative and be able to suggest to sultan’s office feasible idea of coordination with national land use planning. This being action research case, its actual applicability will be verified by initiating activities with Sleman regency government as its main promoter.